Hybrid Mode of Production, Transaction, and Economic Growth: Implication of Digitalization - Biswajit Mandal; Labani Roy Chakraborty; Alapan Sanyal (Global Labor Organization (GLO), 2023)
This essay attempts to build a simple theoretical model of optimization to decipher the effect of digitalization of a part of the entire production structure which we call here trading or transaction or marketing. In the basic model we use traditional Cobb - Douglas production function to argue that a shift from offline to online may induce increase in profit and subsequent economic growth. However, the effects are not uniform implying that factor-input ratio or factor-intensity of the trading activity has a role to play in this context. We also find that night time utilization due to digitalization further strengthens our results. We then extend the basic model for a CES production function. And it has been observed there that in CES - case we have similar results but the channels are a little different for that both revenue and cost have similar consequences of digitalization. Nevertheless, the essence of the basic results holds true even in a more generalized case.
Keywords: D0; D23; D24; D3; O14; O40; 330; Digitalisation; Selling; Output; Profit; Growth